Suscetibilidade a eventos de inundação como subsídio ao planejamento urbano - O estudo da cidade do Crato/Ceará/Brasil - Edmundo Rodrigues de Brito; Frederico de Holanda Bastos (Confins)
Natural hazards in cities represent major challenges in terms of urban planning, requiring a solid theoretical and methodological basis of analysis in order to avoid socioeconomic damage. Through the concept of susceptibility and its applicability in urban planning, the present work proposes a modeling of susceptibility to flood events for the main rivers of the city of Crato/Ceará/Brazil (rivers Granjeiro, Batateiras, Saco do Lobo and Constantino), in due to recurring local problems associated with flood events. Through the combination of statistical techniques, geoprocessing and hydrological analysis, the research proposed for each river under study, three levels of susceptibility to flooding (with a degree of centimetric detail), according to the adopted recurrence time, with five years for the areas of high susceptibility, twenty years for areas of medium susceptibility and one hundred years for areas of low susceptibility. The result indicates sectors of the urban area that have already suffered environmental problems associated with the increase in river water in events of intense precipitation, with emphasis on the areas surrounding the Granjeiro River, in addition to indicating areas with tendencies to present similar problems from the intensification of inappropriate human occupations, thus serving as a subsidy for urban planning with a view to minimizing local natural risks.